Aesthetics, digital studies and Bernard Stiegler - Fitzpatrick, Noel, 1967 December 27-; O'Dwyer, Néill, 1979-; O'Hara, Mick (Michael) (New York, NY : Bloomsbury Academic, 2021)
"A collection of philosophical and aesthetic essays, influenced by Bernard Stiegler, which focuses on the techno-cultural artefact in order to critique, engage, or respond to, an aspect of digital culture"--
'Je suis philosophe' : a personal note to bernard Stiegler / Noel Fitzpatrick -- Digital studies and aesthetics : neganthropology / Bernard Stiegler interviewed by Professor Noel Fitzpatrick -- Introduction. 'Prolegomenon to a digital studies manifesto' / Gerald Moore -- Organology, grammatisation and exosomatic memory in Samuel Beckett's Krapp's last tape / Néill O'Dwyer -- A therapeutics of the image / Michael O'Hara -- The control room imaginary and the production of sovereignty / Cormac Deane -- Film studies between ekphrasis and quotation / Aidan Delaney -- Thirty years : an analysis of the exhibition Art post-internet through the work of Bernard Stiegler with reference to Jean-François Lyotard's exhibition Les Immatériaux / Jeanette Doyle -- Pokémon UNÉSGO : grammatization, gamification and listification in contemporary culture / Connell Vaughan -- Pregnant pause : technological disruption and the neganthropic aesthetics of landscape in Ireland's Borderland / EL Putnam -- Mischievous hermes : digital hermeneutics and Stiegler's Therapeutics / Noel Fitzpatrick.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Description based on online resource; title from digital title page (viewed on August 02, 2021).
eBooks on EBSCOhost
Keywords: Stiegler, Bernard -- Influence; Stiegler, Bernard; Digital media -- Philosophy; Technology -- Philosophy; Aesthetics; Médias numériques -- Philosophie; Technologie -- Philosophie; Media studies; Aesthetics; Digital media -- Philosophy; Influence (Literary, artistic, etc.); Technology -- Philosophy